Investigating of the Effective Factors and Barriers to International Scientific Collaboration from the viewpoint of Nursing Faculty Members - Afshin Mousavi Chelak; Aref Riahi (Majallah-i Bālīnī-i Parastārī va Māmāyī, 2020)
Background & Aims: Proper planning to increase the scientific collaboration of Iranian nursing specialists with the global scientific network in their field can improve the level of this field of healthcare in this country. Therefore, it can upgrade the quality and quantity of nursing services. In this regard, this study aimed to identify the effective factors and barriers to international scientific collaboration from the viewpoint of Nursing Faculty Members. Methods: The present applied research was conducted based on a descriptive survey (cross-sectional) design during the spring and summer of 2020. Statistical population of the study included 249 nursing faculty members whose names are listed in the Iranian Scientometric Information Database. The data were collected through self-report questionnaires with three sections, nine subsections, and 91 items. It should be mentioned that the validity and reliability of the questionnaire were investigated by experts and Chronbach alpha, respectively. The collected data were analyzed using descriptive statistics and statistical tests in SPSS software (version 21). Results: Based on the findings, "communicational factors" and "process-structure factors" with mean scores of 4.03 and 3.87 were the most important barrier and effective incentive (effective factor), respectively, regarding the international scientific collaboration of university members. Moreover, the components of “lack of scientific communication channels to contact foreign researchers and colleagues" and "compatibility between faculty members regarding issues, such as working and writing style" with mean scores of 4.13 and 3.98 were the most important barriers and influencing factors, respectively. Conclusion: Undoubtedly, the development of scientific, educational, and research exchanges between Iranian nursing specialists and their foreign counterparts will lead to scientific progress and development in their field. Therefore, they will be able to provide higher levels of health and nursing services within the health system of our country. Consequently, the faculties, universities, and at the top of them, the Ministry of Health and Medical Education are recommended to develop plans and policies to strengthen effective factors and remove obstacles and challenges.